2020
DOI: 10.1016/j.jnucmat.2020.152173
|View full text |Cite
|
Sign up to set email alerts
|

On the use of charged particles to characterize precipitation in irradiated reactor pressure vessel steels with a wide range of compositions

Abstract: Nuclear reactor lifetimes may be limited by nano-scale Cu-Mn-Ni-Si precipitates (CRPs and MNSPs) that form under neutron irradiation (NI) of pressure vessel (RPV) steels, resulting in hardening and ductile to brittle transition temperature increases (embrittlement). Physical models of embrittlement must be based on characterization of precipitation as a function of the combination of metallurgical and irradiation variables. Here we focus on rapid and convenient charged particle irradiations (CPI) to both: a) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 51 publications
4
20
0
Order By: Relevance
“…MNSPs also develop in low Cu steels, although even trace amounts of Cu are known to be potent catalysts for their formation [53]. The first experimental proof of MNSP formation in irradiated RPV steels was reported in 2004 [54]; and, since then, MNSPs have been widely observed [16,47,50,51,[55][56][57][58]. Notably, CRPs and MNSPs are well predicted by thermodynamic and kinetic modelling [45,46,59].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…MNSPs also develop in low Cu steels, although even trace amounts of Cu are known to be potent catalysts for their formation [53]. The first experimental proof of MNSP formation in irradiated RPV steels was reported in 2004 [54]; and, since then, MNSPs have been widely observed [16,47,50,51,[55][56][57][58]. Notably, CRPs and MNSPs are well predicted by thermodynamic and kinetic modelling [45,46,59].…”
Section: Introductionmentioning
confidence: 90%
“…RPV steel studies have also revealed significant solute segregation to loop and network dislocations. The segregated dislocations are a favoured nucleation sites for heterogeneous nucleation of MNSPs [43,47,50,57,58], as are cascade generated solute cluster complexes. However, apparently random homogeneous nucleation is also frequently observed in RPV steels and is predicted by models at sufficiently high solute contents (supersaturations), particularly Ni.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…phases [47]. Notably the XNis is ≈ 3. previous observations of 425°C PIA after a high dpa neutron irradiation [16].…”
mentioning
confidence: 92%
“…4.3 we compare the volume fraction and radius of CIPs in our 300 • C proton-irradiated specimen with literature on RPV steels with similar copper and high nickel content. This literature data set consists of neutron irradiated and Fe ion irradiated steels spanning over 6 orders of magnitude in dose rate, from neutron dose rates ≈ 0.1 ndpa s −1 matching RPV operational conditions [56][57][58], to Fe ion dose rates up to 150 000 ndpa s −1 [43]. The results from our 300 • C proton irradiation at 880 ndpa s −1 dose rate are found to be in good quantitative agreement with the literature data set, bearing in mind the known effects of nickel (Sec.…”
Section: Discussionmentioning
confidence: 99%